Dependency of the Apparent Contact Angle on Nonisothermal Conditions - Krahl, Rolf; Gerstmann, Jens; Behruzi, Philipp; Bänsch, Eberhard; Dreyer, Michael E. (Physics of Fluids, 2008)
The dynamic behavior of liquids in partly filled containers is influenced to a large extend by the angle between the gas-liquid phase boundary and the solid container wall at the contact line. This contact angle in turn is influenced by nonisothermal conditions. In the case of a cold liquid meniscus spreading over a hot solid wall, the contact angle apparently becomes significantly larger. In this paper we want to establish a quantitative equation for this enlargement, both from experimental and numerical data. Our findings can be used to build a subgrid model for computations, where the resolution is not sufficient to resolve the boundary layers. This might be the case for large containers which are exposed to low accelerations and where the contact angle boundary condition determines the position of the free surface. These types of computation are performed, for example, to solve propellant management problems in launcher and satellite tanks. In this application, the knowledge of the position of the free surface is very important for the withdrawal of liquid and the calculation of heat and mass transfer. © 2008 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.2008.nat.dma.lama3.depend
Keywords: contact angle; capillary flows; contact lines; thermo-capillary flows